PENGARUH PEMBERIAN MINYAK BUAH MERAH (Pandanus conoideus oil) TERHADAP PEMBENTUKAN FOAM CELLPADA AORTA TIKUS GALUR WISTAR (Rattus norvegicus) DENGAN DIET ATEROGENIK - Syarkiah, Syarkiah; Fitri, Loeki Enggar; Pudjirahaju, Astutik (Jurnal Kedokteran Brawijaya, 2008)
Coronary heart disease serves as the main cause of death in the world. One of the effort to reduce therisk of coronary heart disease is by consuming food containing antioxidant. Red fruit contains high antioxidant, namely β-carotine (700 ppm) and alphatocopherol (500 ppm). This study was intended to find out the effect of red fruit oil (Pandanus conoideus oil) toward the formation of foam cell in wistar rat (Rattus norvegicus) with atherogenic diet.This study was an experimental study, the design applied was complete randomized design with 3 repetitions. The treatment in this study wasthe addition of red fruit oil in standard diet andatherogenic one, comprising 8 groups, namely P0group (negative control), P1group (positive control), P2group (standard diet + red Fruit Oil 0,12 ml/day), P3group (standard diet + red Fruit Oil 0,24 ml/day),P4group (standard diet + red Fruit Oil 0,36 ml/day), P5group (atherogenic diet + red Fruit Oil 0,12 ml/day), P6group (atherogenic diet + red Fruit Oil 0,24 ml/day), and P7group (atherogenic diet + red Fruit Oil 0,36 ml/day). The parameter was the number of foam cells. The process and data analysisapplied Oneway Anova statistical test, followed with DMRT (Duncan Multiple Range Test) statistical test.The result of Oneway Anova statistical test indicated that there was a significant difference of foam cell number among groups (p = 0,000). The conclusion inferred from this study is that the addition of red fruit oil with dosage 0.24 ml/day and 0,36 ml/day may significantly obstruct the formation of foam cell in wistar strain rat with atherogenic diet.